PROGNOSIS OF METASTATIC BREAST CANCER: DIFFERENCES BETWEEN PATIENTS WITH DE NOVO AND RECURRENT METASTATIC BREAST CANCER - RASHID , AB; SHAFIQ , B; ISMAIL , Z; SATTAR , MW (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Oncology from January 2021 to January 2022 to evaluate prognostic factors and the prognosis of the patients with recurrent metastatic breast cancer compared to those with de novo metastatic breast cancer. The study was conducted on a total of 400 patients. Patients were categorized into three groups: A) de novo metastatic cancer (MFI < 3 months), B) recurrent metastatic cancer (MFI ⩽24 months), and C) recurrent metastatic cancer (MFI >24 months). The mean follow-up period was 37.2 months, after which 148 (37%) survived. Mean survival in de novo cancer was 30.1 months, and in recurrent cancer was 22.1 months (P=0.14). Subjects with de novo cancer had significantly better survival than those with early metastatic recurrence (MFI <24 months) (P<0.0001). However, the difference between the survival of de novo and late metastatic recurrence (MFI > 24 months) was not statistically significant (P< 0.73). The difference in the impact of prognostic factors among the three metastatic groups was statistically significant (P=0.98). Thus, MFI is a significant prognostic factor for metastatic breast cancer; short MFI indicates an unfavorable prognosis. However, in our study, de novo cancer did not have a very poor prognosis.